Recognition of Single‐Point Mutation Using a Biological Nanopore. Issue 11 (9th August 2020) - Liu, Ping; Kawano, Ryuji
Abstract: Here the recognition of a single‐point mutation in oligonucleotides is described by using nanopore measurements. The translocation behavior of a series of mutated DNA strands, hybridized with a complementary DNA probe, is analyzed via blocking current and unzipping time. Discernment of the mutation position at the single nucleotide level is achieved by analysis of a 2D graph of the bootstrapped translocation data. The proposed approach provides a useful tool for the mutation detection of oligonucleotides secreted from tumor cells and is applicable in simple and label‐free diagnoses as a nanopore liquid biopsy. Abstract : This paper describes the recognition of single‐point‐mutation using nanopore measurements. The unzipping behavior of mutated DNA strands hybridized with the DNA probe analyzed via blocking current and unzipping time. Discernment of the mutation position at a single nucleotide level achieved by scattering the bootstrapped data. The proposed approach is applicable in simple and label‐free mutation diagnoses as nanopore liquid biopsy.